Ultrastructural And Histopathological Studies In Lead Acetate Induced Neurotoxicity In Wistar Albino Rats And Its Amelioration With Ocimum Sanctum (Os) A Leaf Extract - K.SUJATHA; CH.SRILATHA; T.S.CHANDHRASEKHAR RAO; P.AMARAVATHI (International Journal of Pharma and Bio Sciences, 2011)
Lead is a long – known poison of environment and industrial origin. Prolonged exposure damages cellular material and alters cellular genetics and produces oxidative damage. In the present study rats were treated with different doses of lead acetate (60 mgs and 30 mgs / Kg.b.wt. / 3days a week respectively) over a period of 12 weeks and acetyl cholinesterase activity, gross & histopathological changes, and ultrastructural changes were studied in brain. Decreased acetyl cholinesterase activity in lead treated animals was observed. Histopathologically dose dependent changes were observed in brain and revealed severe degenerative changes of neurons, submeningeal haemorrhages, demyelinating changes, capillary proliferation and necrotic nodules were observed in majority of higher doses of lead treated rats. Shrinkage and rounding and loss of purkinje cells in cerebellum were noticed. Ultrastructurally brain revealed swollen and vacuolated vascular endothelial cells, degenerated myelin sheath with interlaminar splitting, empty myelin sheath, decrease in mitochondrial density with degenerative changes, margination and clumping of chromatin in nucleus of lead fed groups. Where as in OS treated groups the similar changes were observed with mild intensiry. However, the altered acetyl cholinesterase activity, histopathological, and ultrastructural changes were dose dependent in the present investigation. . The present experiment suggests that the Ocimum santum exhibited significant protective effect on lead induced brain damage in rats.